Spatio-Temporal Wildland Arson Crime Functions - Butry, David T.
Wildland arson creates damages to structures and timber and affects the health and safety of people living in rural and wildland urban interface areas. We develop a model that incorporates temporal autocorrelations and spatial correlations in wildland arson ignitions in Florida. A Poisson autoregressive model of order p, or PAR(p) model, is estimated for six high arson Census tracts in the state for the period 1994-2001. Spatio-temporal lags of wildland arson ignitions are introduced as dummy variables indicating the presence of an ignition in previous days in surrounding Census tracts and counties. Temporal lags of ignition activity within the Census tract are shown to be statistically significant and larger than previously reported for non-spatial variants of the PAR(p) model. Spatio-temporal lagged relationships with current arson that were statistically significant show that arson activity up to a county away explains arson patterns, and spatio-temporal lags longer than two days were not significant. Other variables showing significance include weather and wildfire activity in the previous six years, but prescribed fire and several variables that provide evidence that such activity is consistent with an economic model of crime were less commonly significant.Resource /Energy Economics and Policy,